Net Foreign Assets and International Adjustment in the United States, Japan and the Federal Republic of Germany. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper examines external adjustment in the U.S., Japan and Germany from the perspective of net foreign asset positions. It asks two questions: What are, in the long run, the determinants of net foreign asset equilibrium? and: What are, in the short run, the adjustment mechanisms sustaining that equilibrium? An analysis of postwar data produces two insights. First, using a cointegration approach, the existence of long-run net foreign asset equilibrium can be identified; in each of the G-3 countries, it is a function of demographic variables and public debt. Second, deviations from the long-run equilibrium give rise to disequilibrium feedback through domestic absorption and through other channels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet